Motivasi, Bimbingan dan Perhatian Orang Tua Siswa dalam Pendidikan di MTs. Baiturrahim Kabar Kecamatan Sakra Lombok Timur - Syahdan Syahdan (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
The purpose of this study is to find out or obtain information or a clear picture of the forms of roles performed by parents of students in helping the success of education, especially Islamic religious education in MTs. Baiturrahim Kabar 2019/2020 Academic Year. The benefits expected in this study can provide benefits for researchers, teachers, and parents of students to create conducive learning facilities, can provide information for parents of students to be able to create a good home environment for their children to pursue and practice the lessons learned. This study was designed in the form of a qualitative study by describing data relating to the variables in this study regarding parental participation in supporting the success of Islamic education in students in MTs. Baiturrahim Kabar. While the study population was all MTs students. NW Baiturrahim Kabar, amounting to 52 students from grade VII to class IX. The instruments used to obtain data are questionnaires / questionnaires, and interviews. The results obtained are the participation of parents in Islamic religious education of their students classified as moderate. This form of parental participation consists in providing motivation, guidance, and attention. Motivation has a very important role in motivating, building the personality and intellect of students to better the future of their children based on the demands of the Islamic religion. The most visible guidance for students is giving advice, giving good ways to get along, speaking well, giving a set of dreams, giving sanctions if guilty. While participation in parents in giving attention to their students to pay attention to all the needs that support learning for their students both within the family and in the wider community.